Lactobacillus paracasei HII01, xylooligosaccharides, and synbiotics reduce gut disturbance in obese rats - Parameth Thiennimitr (2018)
© 2018 Elsevier Inc. Objectives: The beneficial effects of pro-, pre-, and synbiotics on obesity with insulin resistance have been reported previously. However, the strain-specific effect of probiotics and the combination with various types of prebiotic fiber yield controversial outcomes and limit clinical applications. Our previous study demonstrated that the probiotic Lactobacillus paracasei (L. paracasei) HII01, prebiotic xylooligosaccharide (XOS), and synbiotics share similar efficacy in attenuating cardiac mitochondrial dysfunction in obese-insulin resistant rats. Nonetheless, the roles of HII01 and XOS on gut dysbiosis and gut inflammation under obese-insulin resistant conditions have not yet, to our knowledge, been investigated. Our hypothesis was that pro-, pre-, and synbiotics improve the metabolic parameters in obese-insulin resistant rats by reducing gut dysbiosis and gut inflammation. Methods: Male Wistar rats were fed with either a normal or high-fat diet that contained 19.77% and 59.28% energy from fat, respectively, for 12 wk. Then, the high-fat diet rats were fed daily with a 108colony forming unit of the probiotic HII01, 10% prebiotic XOS, and synbiotics for 12 wk. The metabolic parameters, serum lipopolysaccharide levels, fecal Firmicutes/Bacteroidetes ratios, levels of Enterobacteriaceae, Bifidobacteria, and gut proinflammatory cytokine gene expression were quantified. Results: The consumption of probiotic L. paracasei HII01, prebiotic XOS, and synbiotics for 12 wk led to a decrease in metabolic endotoxemia, gut dysbiosis (a reduction in the Firmicutes/Bacteroidetes ratio and Enterobacteriaceae), and gut inflammation in obese-insulin resistant rats. Conclusions: Pro-, pre-, and synbiotics reduced gut dysbiosis and gut inflammation, which lead to improvements in metabolic dysfunction in obese-insulin resistant rats.